A case of punitive damages (genetic engineering). - Klee, M.M (IEEE Engineering in medicine and biology magazine)
This work presents the Rhone-Poulenc Agro vs. DeKalb Genetics Corp case on a genetically engineered corn sold by DeKalb under the trademark Roundup Ready®. The research that led to Roundup Ready corn was done under a joint development/license agreement between Rhone-Poulenc Agro (RPA) and DeKalb. RPA did the genetic engineering, and DeKalb did the greenhouse and field testing of the corn. DeKalb was obligated to report the results of its testing back to RPA, and for a while it did so until early in 1994, DeKalb learned that a particular genetic construct which RPA had prepared, known as RD-12, provided plants with up to four times the normal resistance to the Roundup herbicide. In late 1994, RPA and DeKalb renegotiated their license agreement. Not knowing that the RD-125 construct was so valuable, RPA gave DeKalb a paid-up, worldwide license to its intellectual property covering RD-125, which included the right to sublicense. In essence, RPA gave up all of its exclusive rights to its RD-125 work. In the end, not only did the trial court award millions in damages, but it also rescinded the 1994 license agreement. Roundup Ready corn was thus on the market without a license.